Transoral surgery in larynx and hypopharyngeal hemangiomas in adults - Figueroa, Eduardo; Ianardi, Fabricio; Vega Morejón, Andrés; Ruggeri, Carlos Santiago (Revista del Hospital Italiano de Buenos Aires, 2018)
Hemangiomas are a rare type of benign tumors of the larynx. The treatment is indicated when the tumor produces symptoms (dyspnea, hemoptysis, odynophagia) and also when the risk of severe bleeding from trauma is high. Three hemangiomas of the larynx and hypopharynx were successfully treated transorally with C02 laser and radiofrequency. All were orally fed at 24/48 hours, and none had a tracheostomy The complete resection rate of hemangiomas treated transorally was 100%.